Genome-wide association analysis reveals 6 copy number variations associated with the number of cervical vertebrae in Pekin ducks - Xu, Yaxi; Hu, Jian; Fan, Wenlei; Liu, Hehe; Zhang, Yunsheng; Guo, Zhanbao; Huang, Wei; Liu, Xiaolin; Hou, Shuisheng (Frontiers in Cell and Developmental Biology, 2022)
As a critical developmental stage in vertebrates, the vertebral column formation process is under strict control; however, we observed variations in the number of cervical vertebrae in duck populations in our previous study. Here, we further explored the variations in the number of vertebrae in two duck populations: 421 Pekin duck × mallard F2 ducks and 850 Pekin ducks. Using resequencing data of 125 Pekin ducks with different numbers of cervical vertebrae and 352 Pekin duck × mallard F2 ducks with different numbers of thoracic vertebrae, we detected whole-genome copy number variations (CNVs) and implemented a genome-wide association study (GWAS) to identify the genetic variants related to the traits. The findings verified the existence of variations in the number of cervical vertebrae in duck populations. The number of cervical vertebrae in most ducks was 15, while that in a small number of the ducks was 14 or 16. The number of cervical vertebrae had a positive influence on the neck production, and one cervical vertebra addition could increase 11 g or 2 cm of duck neck. Genome-wide CNV association analysis identified six CNVs associated with the number of cervical vertebrae, and the associated CNV regions covered 15 genes which included WNT10A and WNT6. These findings improve our understanding of the variations in the number of vertebrae in ducks and lay a foundation for future duck breeding.